An Overview of the Therapeutic Effects of Environmental Enrichment on Traumatic Brain Injury - Abayomi Oyeyemi Ajagbe͓; Michael Kunle Ajenikoko; Ebenezer Oyedele Ajiboye (Golestan University Of Medical Sciences, 2021)
Traumatic brain injury (TBI) occurs due to primary or secondary brain damages that result in temporary or permanent neurological deficits. The sum combined rates for TBI-related emergency department visits, hospitalizations, and deaths have escalated in 2001-2010. Environmental enrichment (EE) is a non-invasive therapy used to enhance learning and memory function. Given its positive effects on neuronal plasticity, EE can be applied as therapy for medical conditions such as neurodegenerative disorders (Parkinson's, Alzheimer disease) and TBI. This study reviewed the therapeutic effects of EE via music therapy and mastication for treatment of TBI. The introduction of EE in animal studies has been well established compared to human studies. This entails the use of various objects with different shapes, sizes, colors, textures, running wheels, ropes, plastic tunnels, balls, stairs, and shelters as part of this method that enhance physical activity compared with standard housing. Studies have shown that EE boosts cognitive function after TBI. It is also recommended to use wooden dowels as an EE tool in animal brain research.